1999
DOI: 10.1074/jbc.274.37.26461
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Loss of P2Y2 Receptor Gene Expression on Nucleotide Regulation of Murine Epithelial Cl−Transport

Abstract: Extracellular nucleotides are believed to be important regulators of ion transport in epithelial tissues as a result of their ability to activate cell surface receptors. Although numerous receptors that bind nucleotides have been identified, the complexity of this receptor family, combined with the lack of pharmacological agents specific for these receptors, has made the assignment of particular receptors and ligands to physiological responses difficult. Because ATP and UTP appear equipotent and equieffective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
134
3
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(149 citation statements)
references
References 38 publications
11
134
3
1
Order By: Relevance
“…The P2Y 2 receptor is of pharmacological interest due to its significant potential as a drug target. P2Y 2 receptor knockout mice were found to exhibit defective chloride secretion in airway epithelium in response to ATP and UTP, which suggests that P2Y 2 receptor agonists could function as a treatment for patients suffering from cystic fibrosis by bypassing the defective chloride ion channel cystic fibrosis transmembrane conductance regulator (CFTR) [8]. P2Y 2 receptor agonism may possibly also find application in reducing post-ischemic myocardial damage, since cardioprotective effects were observed for the selective P2Y 2 receptor agonist uridine-5′-tetraphosphate δ-phenyl ester tetrasodium salt (MRS2768, compound 2 in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The P2Y 2 receptor is of pharmacological interest due to its significant potential as a drug target. P2Y 2 receptor knockout mice were found to exhibit defective chloride secretion in airway epithelium in response to ATP and UTP, which suggests that P2Y 2 receptor agonists could function as a treatment for patients suffering from cystic fibrosis by bypassing the defective chloride ion channel cystic fibrosis transmembrane conductance regulator (CFTR) [8]. P2Y 2 receptor agonism may possibly also find application in reducing post-ischemic myocardial damage, since cardioprotective effects were observed for the selective P2Y 2 receptor agonist uridine-5′-tetraphosphate δ-phenyl ester tetrasodium salt (MRS2768, compound 2 in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a variety of experimental approaches have provided evidence that local ATP release and P2RY2 stimulation may inhibit water reabsorption in the collecting duct. 8 Previous studies in mice have identified important functions for P2RY2 in a variety of processes, including nucleotide-regulated Ca 2 þ signalling in lung fibroblasts and airway epithelial cells, 9 nucleotide-stimulated Cl À secretion in the trachea and gallbladder, 10 neuronal growth, 11 stimulation of K þ secretion in the colon 12 and neutrophil chemotaxis. 13 In 2007, Rieg et al 14 reported that saltresistant hypertension occurs in the P2Y2 receptor (mice homologue of the human P2RY2 gene) knockout mice because the baroreceptor response to variations in salt intake remains intact.…”
Section: Introductionmentioning
confidence: 99%
“…As PPADS has some selectivity for P 2 -purinoceptors, we cannot rule out the possibility that electrically-evoked mucosal responses are mediated at least in part by ATP acting through P 1 -purinoceptors. However, active intestinal ion transport has been shown to be modulated predominately by P 2 -purinoceptors (Cressman et al, 1999;Christofi et al, 2004). The lack of effect of thiorphan on this response lends further support for the hypothesis that VIP, substance P and other classes of pro-secretory neuropeptides are not substantially involved in mediating this effect.…”
Section: Discussionmentioning
confidence: 50%